Novel: Playing the Part and Mini-dissertation: The Representation of Modern South African Masculinities in K Sello Duiker’s The Quiet Violence of Dreams - Medalie, David (2026)
Dissertation (MA (Creative Writing))--University of Pretoria, 2016.